Ingestion of Alexandrium pacificum Cysts by a Deposit Feeder: An Option for Ecosystem‐Based Approach Benefiting Aquaculture and Coastal Communities? - Leonardo N. Zamora; Kirsty F. Smith; Jacqui Stuart; D. Tim Harwood; Shenae L. Wales; Emillie M. F. Passfield; Lincoln Mackenzie (New Zealand Journal of Marine and Freshwater Research, 2026)
Harmful algal blooms caused by the paralytic shellfish toxin‐producing species Alexandrium pacificum have increased in recent years in one of the most important aquaculture regions of New Zealand, the Marlborough Sounds. Reoccurring blooms have created large cysts beds in the sediments throughout the sounds. In this region, large populations of the sea cucumber Australostichopus mollis can also be found. These deposit feeders potentially ingest the resting cysts of A. pacificum when feeding. To investigate this, we used molecular techniques to evaluate and quantify cyst ingestion, and chemical analysis to determine toxin accumulation in A. mollis . Results indicate that sea cucumbers can act as bioindicators of cyst distribution through their selective feeding behaviours, with high concentrations of A. pacificum DNA in foregut samples. Sea cucumbers could also serve as a biocontrol tool, as A. pacificum DNA concentrations decreased along the digestive tract, from the foregut to the hindgut, indicating a reduction in cyst number during the digestion process. Furthermore, no toxin accumulation was detected in the sea cucumber tissue. These encouraging results open the possibility for further research to evaluate the efficiency of integrated biocontrol management and the emergence of a multi‐impact aquaculture sector around this iconic New Zealand echinoderm.